(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Memorizing words in a new language, such as Russian, can be challenging due to its unique alphabet and complex grammar. However, modern techniques and technological advancements have significantly enhanced the effectiveness of vocabulary acquisition. This article explores contemporary methods for memorizing Russian words, focusing on mnemonic devices, spaced repetition systems (SRS), mobile applications, immersive learning environments, and gamification. The integration of these strategies offers a comprehensive approach to mastering Russian vocabulary.